Moulana Hasrat Muhani’s Naatia Poetry: مولانا حسرت ؔموہانی کی نعتیہ شاعری - Ejaz Sabir, Dr. Meher Muhammad; Khoso, Professor Dr. Aijaz Ali (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Hasrat Mohani, a prolific poet of his time, left an indelible mark with his Naatia poetry. His verses, steeped in devotion and reverence for the Prophet, resonate with readers to this day. Through the eloquence of his pen, he weaved intricate tapestries of praise for the Chosen One, describing his virtues and teachings with grace and profundity. Mohani’s poetry serves as a spiritual compass, guiding believers towards a deeper connection with their faith. Each line is a testament to his unwavering love for the Prophet, and his words continue to uplift and inspire generations, offering solace in times of spiritual contemplation. In the realm of Naatia poetry, Hasrat Mohani’s work stands as a beacon of devotion and artistic brilliance. His verses are like fragrant flowers, adorning the literary landscape with their beauty. They not only pay homage to the Prophet but also serve as a reminder of the profound impact of faith on one’s creative expression. Mohani’s Naatia poetry, with its timeless relevance and depth of emotion, continues to echo in the hearts of believers, providing a source of inspiration and a path towards spiritual enlightenment. In this way, he has secured his place as a revered poet whose words transcend time and culture. In this paper these aspects in his Naatia poetry are presented.